Molecular Big Data in Sports Sciences: State-of-Art and Future Prospects of OMICS-Based Sports Sciences - Sellami, Maha; Elrayess, Mohamed A.; Puce, Luca; Bragazzi, Nicola Luigi (Frontiers in Molecular Biosciences, 2022)
Together with environment and experience, the biological and genetic make-up of an athlete plays a major role in exercise physiology. Sports genomics has shown, indeed, that some DNA single nucleotide polymorphisms (SNPs) can be associated with athlete performance and level (such as elite/world-class athletic status), having an impact on physical activity behavior, as well as psychological traits. Athletic phenotype is complex and depends on the combination of different traits and characteristics: as such, it requires a “complex science”, like that of metadata and multi-OMICS profiles. Sports genomics could enable to optimize and maximize physical performance, as well as could predict the risk of sports-related injuries. Exercise has an impact on proteome too. Proteomics can assess both from a qualitative and quantitative point of view the modifications induced by training. Recently, scholars have assessed the epigenetics changes in athletes. Summarizing, the different omics specialties seem to converge in a unique approach, termed sportomics or athlomics and defined as a “holistic and top-down”, “non-hypothesis-driven research on an individual's metabolite changes during sports and exercise” (the Athlome Project Consortium and the Santorini Declaration) Not only sportomics includes metabonomics/metabolomics, but relying on the athlete's biological passport or profile, it would enable the systematic study of sports-induced changes and effects at any level (genome, transcriptome, proteome, etc.). However, the wealth of data is so huge and massive and heterogenous that new computational algorithms and protocols are needed, more computational power is required as well as new strategies for properly and effectively combining and integrating data.